Motivasi Kunjungan Konseling Taruna ke Unit Psikologi (Studi Kasus di Politeknik Ilmu Pelayaran Semarang) - Purwantono Purwantono; Eka Susanti (Dinamika Bahari, 2022)
Shipping cadets are intellectuals who enter a period of development as early adults so that the problems they face are quite a lot, such as study problems, future problems, conflicts with family and fellow cadets, therefore the psychology unit is a unit that is very much needed for its existence. The purpose of this study was to analyze the dominant factors that support cadets visiting the psychology unit and the extent to which these factors affect the cadets' visits to the psychology unit. The research method used is quantitative with the research instrument in the form of a questionnaire. The independent variables consist of: (X1) infrastructure facilities with indicators of physical evidence (tangibles); (X2) human resources with indicators of reliability (reliability), responsiveness (responsiveness), assurance (assurance) and attention (empathy); (X3) services with indicators of consultation, film screenings, discussions, book collections, and (Y) as the dependent variable, namely the interest of student visits. The sample used was 60 people from a population of 600 cadets taken by stratified random sampling. The analysis used in this study are: validity, reliability, product moment correlation and chi square. The results of this study indicate that there is a strong relationship between the quality of infrastructure and service quality on the interest of cadets visiting the psychology unit.